Mesenchymal Stromal Cells for Graft Versus Host Disease: Mechanism-Based Biomarkers - Cheung, Tik Shing; Bertolino, Giuliana Minani; Giacomini, Chiara; Bornhäuser, Martin; Dazzi, Francesco; Galleu, Antonio (Frontiers in Immunology, 2020)
The immunosuppressive activity of mesenchymal stromal cells (MSCs) in graft-versus-host disease (GvHD) is well documented, but their therapeutic benefit is rather unpredictable. Prospective randomized clinical trials remain the only means to address MSC clinical efficacy. However, the imperfect understanding of MSC biological mechanisms has undermined patients’ stratification and the successful design of clinical studies. Furthermore, although MSC efficacy seems to be dependent on patient-associated factors, the role of patients’ signature to predict and/or monitor clinical outcomes remains poorly elucidated. The analysis of GvHD patient serum has identified a set of molecules that are associated with high mortality. However, despite their importance in defining GvHD severity, their role in predicting or monitoring response to MSCs has not been confirmed. A new perspective on the use of MSCs for GvHD has been prompted by the recent findings that MSCs are actively induced to undergo apoptosis by recipient cytotoxic cells and that this process is essential to initiate MSC-induced immunosuppression. This discovery has not only reconciled the conundrum between MSC efficacy and their lack of engraftment, but also highlighted the determinant role of the patient in promoting and delivering MSC immunosuppression. In this review we will revisit the extensive use of MSCs for the treatment of GvHD and will elaborate on the need that future clinical trials must depend on mechanistic approaches that facilitate the development of robust and consistent assays to stratify patients and monitor clinical outcomes.